Biomechanical Analysis of Fixation Devices for Basicervical Femoral Neck Fractures. Issue 1 (1st January 2019) - Johnson, Joseph; Deren, Matthew; Chambers, Alison; Cassidy, Dale; Koruprolu, Sarath; Born, Christopher
Abstract : Introduction: Basicervical femoral neck fractures are challenging fractures in geriatric populations. The goal of this study was to determine whether compression hip screw (CHS) constructs are superior to cephalomedullary constructs for the treatment of basicervical femoral neck fractures. Methods: Thirty cadaver femurs were osteotomized and received a CHS with derotation screw, a long cephalomedullary nail (long Gamma nail), or a short cephalomedullary nail (short Gamma nail). All constructs were loaded dynamically in compression until dynamic failure. Results: All failed CHS constructs demonstrated superior femoral head cutout. In the long Gamma nail and short Gamma nail groups, constructs failed by nail cutout through the medial wall of the trochanter or rotationally. Normalized fluoroscopic distance was found to increase markedly with an increasing cycle count when considering all treatment groups. Conclusions: Given our results and those of previous studies, we could not determine superiority of one implant and recommend that surgeons select fixation constructs based on the individual patient's anatomy and the surgeon's comfort with the implant.